Children’s Hedonic Judgments of Cigarette Smoke Odor: Effects of Parental Smoking and Maternal Mood - Forestell, Catherine A. (2005)
Age-appropriate tasks were used to assess 3-to 8-year-old children’s liking, identification, and preference for a variety of odors, including that of exhaled cigarette smoke. Children whose parents smoke took longer to decide whether they liked the cigarette odor and were significantly more likely to prefer the odor of cigarette to the neutral and unfamiliar odor of green tea compared with children of nonsmokers. Among children of smokers, relative preferences for the cigarette odor were related to maternal mood disturbance and depression scores. These findings suggest that some early learning about cigarette smoke odor is based on sensory experiences at home and anchors it to the emotional context in which their mothers smoke.